Pelatihan Budidaya Tanaman Sayuran Menggunakan Metode Hidroponik Dengan Memanfaatkan Botol Bekas Sebagai Media Tanam - Ningsih, Winnarti; Billah, Mu'tasim; Laily, Dona Waahyuning (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Vegetables play an important role for humans, because they contain little fat and carbohydrates, but contain lots of vitamins, nutrients that are very important for health. Hydroponics is a method of cultivating plants that only requires water as a growing medium without using soil. The use of this hydroponic concept is a simple method that can be used to increase people's attention to the environment by using used bottles. Based on the things that have been described, the author raises the topic of community service entitled "Training of Vegetable Cultivation Using the Hydroponic Method Using Used Bottles as Hydroponic Growing Media in Karangan Village, Bareng District, Jombang Regency". The target of this community service activity is PKK Karangan Village, Bareng District, Jombang Regency, East Java Province in May 2023. The method used in this activity is to socialize, namely providing information and understanding about how to grow vegetables using the system hydroponics along with using used bottles for hydroponic growing media. This socialization was carried out by practicing growing vegetables with tools and materials in the form of vegetable seeds, rockwool, flannel cloth, used bottles, and AB MIX nutrition. The steps for making hydroponics begin with making planting media from used bottles. The preparation of the material was also carried out by direct practice, namely by using tools and materials to make hydroponic frameworks from used bottles with the aim of facilitating socialization. From this activity it can be concluded that it can provide information, knowledge and skills to PKK mothers about the benefits of planting vegetables using the simple hiroponic method from used bottles and minimizing used bottle waste in the community.